An application of the analytic hierarchy proceá method in farmland appraisal - Aznar Bellver, J.=700 1 Caballer Mellado, V.
(Es, En)
ilus., 32 ref.
Keywords: METODOS ESTADISTICOS; ANALISIS DE DATOS; VALOR ECONOMICO; SECTOR AGRARIO; ESPAÑA; VALORACION AGRARIA